Pemberdayaan Masyarakat Sadar Hukum sebagai Upaya Pencegahan Tindak Pidana Khusus melalui Program Keluarga Sadar Hukum di Kelurahan Baru Ulu, Kota Balikpapan - Edys Panto Simanjuntak; Rosdiana Rosdiana; Ana Fatmawati Angraini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This community service activity aims to empower the community to have legal awareness as a preventive strategy in preventing specific crimes, both those that occur directly or through digital media. The phenomenon of violence or vigilantism, which is increasingly widespread in society, reflects a low understanding of the law, the dominance of social emotions, and distrust of formal law enforcement mechanisms. In the digital era, this behavior has also developed into online violence, such as the spread of shame, insults, and threats through social media, which has the potential to give rise to cybercrimes as regulated in the Electronic Information and Transactions Law. This activity was carried out through the Legal Awareness Family Socialization (Kadarkum) program in Baru Ulu Village, Balikpapan City, East Kalimantan, using legal counseling methods, participatory discussions, and educational approaches based on local social and cultural values. The targets of the activity were the general public, community leaders, and families as the smallest social unit in the formation of a legal culture. The results of the activity showed an increase in public understanding regarding the legal consequences of vigilantism, both in physical and digital contexts. Furthermore, the public is beginning to show a shift in attitudes toward more rational, legal-oriented problem-solving, and increased self-control in responding to social conflict. These activities contribute to building a legal culture that is more aware, preventative, and adaptive to legal challenges in the digital era.